2014
DOI: 10.1038/nrc3789
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell survival during detachment from the ECM: multiple barriers to tumour progression

Abstract: Epithelial cells require attachment to the extracellular matrix (ECM) for survival. However, during tumour progression and metastasis, cancerous epithelial cells must adapt to and survive in the absence of ECM. During the past 20 years, several cellular changes, including anoikis, have been shown to regulate cell viability when cells become detached from the ECM. In this Opinion article, we review in detail how cancer cells can overcome or take advantage of these specific processes. Gaining a better understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
285
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 317 publications
(293 citation statements)
references
References 144 publications
5
285
1
2
Order By: Relevance
“…The survival of cancer cells during ECM detachment requires rectifying ECM-detachment-induced loss of ATP generation (accomplished in this case by Ras-mediated SGK-1 activation) and blocking caspase activation (anoikis). 4 Given that we did not discern a role for Ras-mediated SGK-1 signaling in anoikis regulation (Figure 2f and Supplementary Figures S3B, S3C, S4B and S4C), we hypothesized that oncogenic Ras may use a distinct signaling pathway to block anoikis. Indeed, oncogenic Ras (either H-Ras or K-Ras) can effectively inhibit caspase-3/7 activation (Figure 5a) and promote cell viability (Figure 5b) during ECM detachment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The survival of cancer cells during ECM detachment requires rectifying ECM-detachment-induced loss of ATP generation (accomplished in this case by Ras-mediated SGK-1 activation) and blocking caspase activation (anoikis). 4 Given that we did not discern a role for Ras-mediated SGK-1 signaling in anoikis regulation (Figure 2f and Supplementary Figures S3B, S3C, S4B and S4C), we hypothesized that oncogenic Ras may use a distinct signaling pathway to block anoikis. Indeed, oncogenic Ras (either H-Ras or K-Ras) can effectively inhibit caspase-3/7 activation (Figure 5a) and promote cell viability (Figure 5b) during ECM detachment.…”
Section: Resultsmentioning
confidence: 99%
“…ATP generation) in addition to blocking caspase activation (anoikis) to survive during ECM detachment, 4 it is critically important to understand the precise molecular mechanisms involved in mediating both anoikis and metabolism. The data described here outline a unique, multifaceted signaling pathway operating downstream of oncogenic Ras to permit anoikis inhibition and stimulate ATP production ( Figure 8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 It has become clear that tumor progression and metastasis require cancer cells to inhibit anoikis, oftentimes through alterations in intracellular signaling pathways. [18][19][20] Interestingly, previous studies have shown that ErbB2 and EGFR, which are hyperactivated in a substantial percentage of IBC patients, 21 can effectively antagonize the anoikis program to facilitate anchorage-independent growth. [22][23][24][25][26][27][28] However, a detailed examination of the molecular mechanisms underlying anoikis inhibition in IBC cells has yet to be completed.…”
mentioning
confidence: 99%